Comparison of the effects of EPA and DHA alone or in combination in a murine model of myocardial infarction. (August 2016) - Madingou, Ness; Gilbert, Kim; Tomaro, Leandro; Prud'homme Touchette, Charles; Trudeau, François; Fortin, Samuel; Rousseau, Guy
Abstract: The aim of this project was to investigate the impact of two dietary omega-3 polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), alone or in combination, on infarct size. Adult, male Sprague-Dawley rats were fed for 14 days with different omega-3 diets. The animals were subjected to ischemia for 40 min followed by reperfusion. Infarct size, Akt (protein kinase B) activation level, caspase-3 activity and mitochondrial permeability transition pore (mPTP) opening were measured. The results indicate that EPA or DHA alone significantly reduced infarct size compared to the other diets. Akt activity was increased in the group fed EPA or DHA alone, whereas no significant activation was observed in the other groups compared to no omega-3 PUFA. DHA alone reduced caspase-3 activity and conferred resistance to mPTP opening. In conclusion, our results demonstrate that EPA and DHA are individually effective in diminishing infarct size in our experimental model while their combination is not. Highlights: Addition of 5 g/kg eicosapentaenoic acid (EPA) in the diet reduces infarct size. Addition of 5 g/kg docosahexaenoic acid (DHA) in the diet reduces infarct size. Addition of 5 g/kg of both EPA and DHA does not reduce infarct size. Activation of Akt is superior in the ischemic myocardium in presence of DHA or EPA. DHA alone reduced caspase-3 activity and conferred resistance to mPTP opening.